Relação médico-paciente: avaliação do compromisso profissional médico na visão do paciente - NASCIMENTO, Gutierry Alexandro Almeida do (2022)
In the current medicine, many factors have contributed for the distance and mechanization of the doctor-patient relationship, as the grown specialization of medical practice, the capitalistic politics adopted by the plans of health, the technological advances, or even the relative deficiencies of the formation and education in the medical schools. The regaining of humanistic practices as an essential and complementary tool to the new resources and needs of the medicine is becoming a worldwide tendency. This research analyzes, from the view of the patient, the doctor-patient relationship, giving emphasis to the professional commitment, that is, the responsibility of the doctor in the human side of medicine. With this, were realized interviews with 147 patients, using a closed questionnaire after the consultation, identifying and listing the prevalence of the main told complains and verifying the satisfaction and trust of the patients with the doctor. Clinical appointments that lasted less than 10 minutes was the most prevalent complain (28,57%; n=42). However, the majority of the patients (72,79%; n=107) showed satisfied and with a good impression about the professional commitment of the doctor. Based on the results, this research demonstrates the main points of fragility for the reflection and search for solutions in order to find the best possible way to humanize the practice of the great art that is the exercise of the medicine.